PENGARUH USIA, GENDER, LINGKUNGAN DAN PENDIDIKAN TERHADAP LITERASI KEUANGAN SYARIAH UMKM (STUDI KASUS USAHA KECIL PEDAGANG ANGKRINGAN DI KABUPATEN DEMAK) - Nafiatul Lia (JASIE, 2022)
This study aims to contribute to the knowledge of Islamic finance in angkringan traders, especially related to business sustainability according to Islamic sharia by increasing sharia financial literacy which can be seen from age, gender, environment and education. The number of samples as many as 80 respondents with simple random sampling method. Sources of data used in the form of primary data and secondary data. The data analysis method used is multiple regression with SPSS. The results of the study found that gender, environment and education partially have a positive and significant influence on Islamic financial literacy. Meanwhile, age partially has no effect on Islamic financial literacy. And simultaneously age, gender, environment and education have a significant influence on the level of Islamic financial literacy. The implication of this research is that it can provide information about financial management according to Islamic law so that it will help the community, especially MSME actors in short-term and long-term financial planning and have broader knowledge and insight.Keywords: age, gender, environment, education and Islamic financial literacy